PENGARUH KETINGGIAN TEMPAT TERHADAP KANDUNGAN PROKSIMAT DAN KOMPOSISI ASAM OKSALAT PADA KULIT UMBI TALAS BENENG (Xanthasoma undipes K.Kock) YANG DIBUDIDAYAKAN - Eltis Panca Ningsih; Nuniek Hermita (Jurnal Agroekoteknologi, 2016)
Talas beneng (Xanthosoma undipes K. Koch) is the local taro from Mountain Coral of Banten Province. This research was aimed to know the nutrient content, composition, oxalic acid and mineral content in the talas beneng skin are cultivated by the community at different places. The research was carried out from May until October 2016. This research was conducted in the form of field research around the area of Mountain Coral, Pandeglang Regency, Banten Province. Analysis of the talas beneng skin was done in Balai Besar Industri Agro (BBIA), Bogor. The results showed that the content of proksimat talas beneng skin was cultivated include water, ash, protein, fat and carbohydrates. Moisture content at a higher altitude 500 m above sea level (asl): (87,6%) compared to the height of 400 m dpl (84,6%). Ash at altitudes of 400 m asl was higher (1,92%) compared to the height of the 500 m asl (1.53%). Protein content (1.04%) and fat (0.25%) at an altitude of 500 m asl was higher compared to the height of 400 m asl (1.00% and 0.23%). Carbohydrate content (12.2%) at an altitude of 400 m asl higher than the height of the 500 m asl (9.58%). Content of oxalic acid (0,19%) at an altitude of 400 m asl higher than the height of the 500 m asl (0.12%).Keywords: elevation, proximate, oxalic acid, talas beneng